ENVIRONMENTAL QUALITY AND ITS CHANGES ESTIMATION ON THE EXAMPLE OF TATARSTAN REPUBLIC NATURAL RESERVED FOND OBJECTS - G. R. Valeeva; M. V. Karpov (Юг России: экология, развитие, 2017)
Aim. Environment quality estimation and its probable changes in the presence of anthropogenous influence on the Tatarstan republic natural reserved fond objects with fluctuating asymmetry method on different species of organisms was carried out.Methods. Gathering of scientific material was carried out at the 2012-2013 years period at the natural reserved fond objects territory – Tatarstan republic state natural complex wildlife areas. For land ecosystems estimation the morphometric parameters of birch leafs was used, for water ecosystems characteristic – the morphometric parameters of most ordinary species of fish (small fry, golden crucian, bream) and amphibians (pond and lake frog). Morphometric measurements results of indicator organisms was statistically processed, fluctuating asymmetry parameter was calculated, according received results the state of ecosystems was estimated.Results. The state of some especially protected natural areas at the Tatarstan republic was estimated. Applicability of fluctuating asymmetry parameter for complex ecosystem estimation was proved. Received results can be used as a matter for ecological risk estimation methodic developing for Tatarstan republic territory.Main conclusions. The investigated areas ecological status was estimated as “relatively normal”. The fluctuating asymmetry parameter in similar conditions for phytoindicator was higher than for zooindicators Results analysis was shown the need of using different indicators for complex characteristic of environmental quality.